2015
DOI: 10.1016/j.jsps.2014.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of HPMC and mannitol on drug release and bioadhesion behavior of buccal discs of buspirone hydrochloride: In-vitro and in-vivo pharmacokinetic studies

Abstract: Delivery of orally compromised therapeutic drug molecules to the systemic circulation via buccal route has gained a significant interest in recent past. Bioadhesive polymers play a major role in designing such buccal dosage forms, as they help in adhesion of designed delivery system to mucosal membrane and also prolong release of drug from delivery system. In the present study, HPMC (release retarding polymer) and mannitol (diluent and pore former) were used to prepare bioadhesive and controlled release buccal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 43 publications
2
27
0
Order By: Relevance
“…It was found that the amount dissolved of TML was increased by using polymer in concentration of 250 mg when compared with using 400 mg polymer. It was reported that the increase in polymer proportion will consequently increases the viscosity of gel layer and also results in gel layer with longer diffusional path length resulting in greater retardation of drug release . Polymer type (X c ) was found to affect the per cent of drug dissolved significantly.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the amount dissolved of TML was increased by using polymer in concentration of 250 mg when compared with using 400 mg polymer. It was reported that the increase in polymer proportion will consequently increases the viscosity of gel layer and also results in gel layer with longer diffusional path length resulting in greater retardation of drug release . Polymer type (X c ) was found to affect the per cent of drug dissolved significantly.…”
Section: Resultsmentioning
confidence: 99%
“…HPMC is a biodegradable and biocompatible excipient, generally recognized as safe by the US Food and Drug Administration (FDA). It is widely used in pharmaceutical formulations [ 55 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…The swollen tablets and patches were then reweighed (W2). This experiment was performed in triplicate [25]. The degree of swelling (water uptake) was calculated according to the following formula:…”
Section: Swelling Studymentioning
confidence: 99%